2020
DOI: 10.1002/eji.201948442
|View full text |Cite
|
Sign up to set email alerts
|

Negative control of diacylglycerol kinase ζ‐mediated inhibition of T cell receptor signaling by nuclear sequestration in mice

Abstract: Diacylglycerol kinases (DGKs) play important roles in restraining diacylglycerol (DAG)‐mediated signaling. Within the DGK family, the ζ isoform appears to be the most important isoform in T cells for controlling their development and function. DGKζ has been demonstrated to regulate T cell maturation, activation, anergy, effector/memory differentiation, defense against microbial infection, and antitumor immunity. Given its critical functions, DGKζ function should be tightly regulated to ensure proper signal tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 88 publications
(123 reference statements)
0
2
0
Order By: Relevance
“…We have recently found that downregulation of DAG-mediated signaling and tight control DAG by DGKα/ζ is important for MAIT cell maturation. Overexpression of WT DGKζ ( Dgkz wt ) or a gain-of-function mutant of DGKζ ( Dgkz ΔNLS ) in developing thymocytes cause modest or severe inhibition of MAIT cell maturation 27 , 62 . We further examined MAIT1 and MAIT17 cell differentiation in these mice.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have recently found that downregulation of DAG-mediated signaling and tight control DAG by DGKα/ζ is important for MAIT cell maturation. Overexpression of WT DGKζ ( Dgkz wt ) or a gain-of-function mutant of DGKζ ( Dgkz ΔNLS ) in developing thymocytes cause modest or severe inhibition of MAIT cell maturation 27 , 62 . We further examined MAIT1 and MAIT17 cell differentiation in these mice.…”
Section: Resultsmentioning
confidence: 99%
“…Masaru Taniguchi, Kim Nichols, and Luc Van Kaer. Dgkz WT -Cd4Cre and Dgkz ΔNLS - Cd4Cre mice with T cell-specific expression of WT-DGKζ or a gain-of-function DGKζ ΔNLS mutant were recently reported 27 , 62 . Primers for mouse genotyping are listed in supplementary Table 1 .…”
Section: Methodsmentioning
confidence: 99%